Absorption of nutrients, growth and nutritional disorders resulting from ammonium toxicity in rice and spinach plants - Silva, Gilmara Pereira da [UNESP]; Prado, Renato de Mello [UNESP]; Soares Ferreira, Ricardo Perri [UNESP] (United Arab Emirates Univ, 2016)
Excess nitrogen in the ammonium form may induce different nutritional disorders in plants depending on the species cultivated. The present study sought to evaluate the accumulation of nutrients, growth and visual symptoms in rice and spinach plants in function of the ammonium concentrations. Two experiments were performed with rice and spinach plants in a greenhouse, at the Universidade Estadual Paulista Julio de Mesquita Filho, Campus of Jaboticabal-SP, Brazil. In each experiment five ammonium concentrations were used (10, 20, 40, 80 and 100 mmol L-1), arranged in a randomized block design with five repetitions. The effects of excess ammonium were studied on the green color index, electrolyte leakage, accumulation of N, Mg, K and Ca in the shoots, leaf area, height, dry matter of root, shoots and whole plant, and characterization of the visual symptoms of toxicity in the plants. These effects of excess ammonium reported above are reflected in the production of plant dry matter, with a linear decrease in dry matter of the roots, shoots and whole plant. Excess ammonium in the nutrient solution decreased the accumulation of dry matter due to reduced leaf area and increased cellular electrolyte leakage which induced symptoms characteristic of ammonium toxicity in both species, and also decreased uptake of Ca, Mg and K in rice plants and only Ca in spinach plants.
Keywords: Abiotic stress; Ammonium nutrition; Plant species; Oryza sativa; Spinacia oleracea